Pembiasaan Membaca Al-Qur’an Pada Siswa: Sebuah Upaya Menanamkan Pendidikan Karakter di SDN 1 Sidamulya Cirebon - Uswatun Hasanah; Mucharam Cholil (Tarbawiyah Jurnal Ilmiah Pendidikan, 2019)
Educational institutions as one of the places for the formation of human personality have a great responsibility towards fostering student character. Character education is very important to instill early on so students can behave well. The purpose of this study is to describe the character education carried out by the teacher through the habituation of students in reading the Qur'an at SD Negeri 1 Sidamulya. The research technique used is a qualitative approach. Character education starts from the teacher who gives a good example, so students will be enthusiastic in doing any activities in the school. Among the forms of inculcation of character education through the habituation of reading the Koran in SDN 1 Sidamulya Cirebon Regency, including: Teachers instill the value of character education in the form of responsibility by giving assignments; The teacher instills religious values, that is, the teacher and students together to do the Dhuha Prayer and study the Qur'an in the mosque; The teacher instills the value of Discipline, that is the activity of reading the Qur'an every day in the school yard; The teacher instills democratic values ​​by creating an atmosphere of learning interaction that is built on love.